2017
DOI: 10.1016/j.snb.2017.03.092
|View full text |Cite
|
Sign up to set email alerts
|

Dye-assembled nanocomposites for rapid upconversion luminescence sensing of Cu2+

Abstract: An upconversion luminescence probe for the detection of Cu 2+ is constructed by assembling meso-tetra(4-sulfonatophenyl)porphine dihydrochlorid (TSPP) on SiO 2-encapsulated β-NaYF 4 :Yb,Er,Gd nanorods which were synthesized by hydrothermal reaction and encapsulated with a layer of ultrathin silica through a water-in-oil reverse microemulsion strategy. Under excitation of 980 nm, the nanorods emit upconversion lights at 545 nm and 659 nm, respectively. While in the presence of Cu 2+ , Cu 2+ forms complex with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…The LOD is calculated using the formula 3δ/ S where δ denotes standard deviation and S is the slope. The LOD of Cu 2+ ions using current PAA-UCNPs based sensor is as low as 0.1 μM, which is superior to that of existing upconversion Cu 2+ detection methods (Sarkar et al, 2014 ; Huang et al, 2017 ). Also, the LOD of the current PAA-UCNPs platform is comparable with the values reported in the literature (Wang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…The LOD is calculated using the formula 3δ/ S where δ denotes standard deviation and S is the slope. The LOD of Cu 2+ ions using current PAA-UCNPs based sensor is as low as 0.1 μM, which is superior to that of existing upconversion Cu 2+ detection methods (Sarkar et al, 2014 ; Huang et al, 2017 ). Also, the LOD of the current PAA-UCNPs platform is comparable with the values reported in the literature (Wang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 82%
“…Also, the LOD of the current PAA-UCNPs platform is comparable with the values reported in the literature (Wang et al, 2014 ). The meso-tetra(4-sulfonatophenyl)porphine dihydrochlorid (TSPP) on SiO 2 -encapsulated NaYF 4 :Yb,Er,Gd UCNPs based platform for the detection of Cu 2+ ions with a LOD of 2.16 μM was reported by the Huang et al ( 2017 ). These results indicate that the current PAA-UCNPs based platform exhibits superior sensitivity for Cu 2+ detection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cu 2+ is the third abundant trace metal ion in human body and many researches on Cu 2+ detection have been reported. Cai and co‐workers constructed a novel probe by assembling dyes onto SiO 2 ‐coated upconversion nanorods and found that Cu 2+ can combine with the dye and quench the UCL. Shi and co‐workers employed the similar strategy to detect Cu 2+ and applied this detection in living cells .…”
Section: Ucnp‐based Nanoprobes For Different Analyte Detectionmentioning
confidence: 99%